Child acceptance-rejection behaviors of lower and upper socioeconomic status mothers - Erkan, Nefise Semra; TORAN, MEHMET (Scientific Journal Publishers, 2010)
In this study we sought to show the difference between the child acceptance-rejection behaviors of lower and upper socioeconomic status mothers, and establish whether or not their acceptance-rejection behaviors were affected by their age, and the number and sex of their children. A total of 246 mothers living in Diyarbakır, 123 with lower and 123 with upper socioeconomic status, was enrolled in the study. Data were gathered by using a personal information form and the Parental Acceptance-Rejection Questionnaire-Mother Form (Rohner, Saavedra, & Granum, 1980). The results revealed a significant difference between lower and upper socioeconomic status mothers' child acceptance-rejection behaviors (t = 7.709; p < 0.05). While the mothers' age (r = .202; p < 0.05) and number of children (r = .238; p < 0.01) were positively correlated to their acceptance-rejection behaviors, their children's sex did not make a significant difference to the mothers' acceptance-rejection behaviors.
Keywords: Children; Mother; Parental Acceptance; Parental Acceptance-Rejection Questionnsire; Parental Rejection; Socioeconomic Status